1990
DOI: 10.1557/proc-198-609
|View full text |Cite
|
Sign up to set email alerts
|

Surface Phase Separation and Ordering in Compound Semiconductor Alloys

Abstract: The orientation dependence of phase separation has been examined in detail in InGaAsP layers grown by liquid phase epitaxy on (001), (110), (111)In and (123) InP substrates. It is shown that phase separation is two-dimensional in nature and does not occur along the growth direction for the cases examined. Further, phase separation takes place along the soft directions lying in the growth plane. These results very strongly suggest that phase separation evolves at the surface while the layer is growing.CuPt-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Samples #1 and #2, which were grown under higher susceptor rotation frequency (9 rpm), had lower VCM periods (3.4 and 3.5 nm) than those grown at 6 rpm, which had higher VCM periods (around 4.6 nm). Thus, our results indicate that the VCM is correlated to the susceptor rotation period and should be attributed to inhomogeneities in the reactor chamber [6] On the other hand, the LCM, with periods ranging in tens of nanometers, is probably caused by a strain field existing at the epitaxial surface [7,8]. This is more possible because bulk diffusion coefficients of the constituting elements are too low to explain the length scales of the observed compositional modulation [8].…”
Section: Resultsmentioning
confidence: 75%
“…Samples #1 and #2, which were grown under higher susceptor rotation frequency (9 rpm), had lower VCM periods (3.4 and 3.5 nm) than those grown at 6 rpm, which had higher VCM periods (around 4.6 nm). Thus, our results indicate that the VCM is correlated to the susceptor rotation period and should be attributed to inhomogeneities in the reactor chamber [6] On the other hand, the LCM, with periods ranging in tens of nanometers, is probably caused by a strain field existing at the epitaxial surface [7,8]. This is more possible because bulk diffusion coefficients of the constituting elements are too low to explain the length scales of the observed compositional modulation [8].…”
Section: Resultsmentioning
confidence: 75%
“…For the In x Ga 1-x As y P 1-y /InP system, a phase separation at the surface during epitaxial growth exists, also referred to as lateral composition modulation (LCM). [30][31][32][33] Specifically, LaPierre et al [30] found that a preferential sticking of P atoms to Ga sites and of As to In takes place, which results in the formation of GaP and InAs-rich areas. They also found that LCM is strongly dependent on the InGaAsP surface orientation and composition, being more pronounced for the (100) orientation and for 1.3 μm bandgap wavelength, which corresponds to the case investigated here.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, a thin homogeneous strained layer would be unstable and will tend to relax the strain by buckling. In particular, several authors [15] argue that the buckling is promoted by the existence of the fine modulation. They associate the coarse modulation to this buckling.…”
Section: Composition Modulation Versus Strain Modulationmentioning
confidence: 99%